Characteristic and Survival Analysis of Infants with Critical Congenital Heart Disease - Talib, Suprohaita Rusdi; Siswanto, Johanes Edy; Djer, Mulyadi M; Safanta, Nurzalia; Nurhakiki, Syifa; Taufiqurahman, Khobir Abdul Karim; Adisasmita, Asri (UI Scholars Hub, 2025)
Congenital heart disease (CHD) is a major health concern worldwide. This study focused on survival analysis and the factors influencing survival in infants with critical congenital heart disease (CCHD). A total of 79 infants diagnosed with CCHD were identified, with 48.1% (n=38) exhibiting duct-dependent pulmonary circulation, 35.6% (n=28) exhibiting duct-dependent systemic circulation, 6.3% (n=5) exhibiting critical non-duct-dependent, and 10.2% (n=8) exhibiting parallel circulation issues. Of the infants studied, 55.7% (n=44) were male, 78.5% (n=62) had a gestational age of ≥37 weeks, 62% (n=49) had a birth weight of ≥2,500 grams, 59.5% (n=47) exhibited normal fetal growth, 93.7% (n=74) experienced no asphyxia, 91.1% (n=72) had no other congenital disabilities, 87.3% (n=69) had no history of fetal distress, 58.2% (n=46) maintained normal oxygen saturation, and 88.6% (n=70) had an extended stay in the neonatal intensive care unit. The survival analysis indicated that the prognosis of newborns with CCHD was markedly affected by gestational age, birth weight, desaturation, respiratory distress, and hereditary abnormalities. Additional study is required to assess the risk factors influencing the survival of newborns with CCHD.